Effect of Beer Marinades on Formation of Polycyclic Aromatic Hydrocarbons in Charcoal-Grilled Pork - Viegas, Olga (2014)
The effect of marinating meat with Pilsner beer, nonalcoholic Pilsner beer, and Black beer (coded respectively PB, P0B, and BB) on the formation of polycyclic aromatic hydrocarbons (PAHs) in charcoal-grilled pork was evaluated and compared with the formation of these compounds in unmarinated meat. Antiradical activity of marinades (DPPH assay) was assayed. BB exhibited the strongest scavenging activity (68.0%), followed by P0B (36.5%) and PB (29.5%). Control and marinated meat samples contained the eight PAHs named PAH8 by the EFSA and classified as suitable indicators for carcinogenic potency of PAHs in food. BB showed the highest inhibitory effect in the formation of PAH8 (53%), followed by P0B (25%) and PB (13%). The inhibitory effect of beer marinades on PAH8 increased with the increase of their radical-scavenging activity. BB marinade was the most efficient on reduction of PAH formation, providing a proper mitigation strategy.